Gambaran Pola Asuh Orang Tua Pada Anak Prasekolah Di Dusun Sadang Timur DesaSadang Timur Taman Sidoarjo - Purwati, Heni; Rosyida & Titik Rahmawati, Novi (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractParenting is a challenging task for parents, especially new parents. Parenting requires a number of interpersonal skills and have a great emotional demands, but so little formal education regarding this task. Most parents learn parenting practices from their own parents. This research is to indcntily a picture of parenting parents on preschool in Dusun Sadang Timur Taman Sidoarjo. This study design is descriptive with parenting researchers variable. The population is all parents who have preschool-aged children in Dustin Sadang Timur Taman Sidoarjo, the sampling technique by purposive sampling and obtained a sample or 63 parents who have preschool-aged children. Data was collected by questionnaires parenting parents by measuring two dimensions that relation dimension and guidance dimension then the data is collected then analyzed the data presented in the form of frequency distribution. Result was found most respondents have a democratic parenting style as much as 51 respondents (81,0%). Tt is influenced by several factors that one of which is the age of parents. Age has a god reasons in realtion to the readiness to parents. In addition to the level of education can also affect parenting someone due to the level of higher education its mean the higher the parents can receive all information from the outside, especially on how to care good.Keyword: parenting parents, preschool child.